Comparison of the effect of oral multiple dose with single intramuscular vitamin K1 administration on prothrombin time in term baby - Nancy Ervani; Bugis M. Lubis; Emil Azlin; Guslihan D. Tjipta; Lily Emsyah (Paediatrica Indonesiana, 2009)
Background Vitamin K deficiency can cause bleeding disorders inhealthy breastfed infants. The efficacy of newborn intramuscularvitamin K prophylaxis for the prevention of this bleeding problemhas been well established, but this is an invasive procedure. Oralvitamin K prophylaxis is more effective, less expensive, and lesstraumatic than intramuscular administration.Objective To compare prothrombin time (PT) after theadministration of oral multiple dose vitamin K1 with that afteran intramuscular preparation.Methods Infants were randomised at birth into the intramuscular(IM) group (1 mg vitamin K1) and the oral group (2 mg given atbirth and repeated at day 3). PT was monitored before and afterthe administration of vitamin K1.Results Thirty six of 70 infants received oral vitamin K1. MeanPT (SO) before vitamin K1 administration was 36.34 (SO 20.03)seconds in oral group and 31.96 (SO 25.51) seconds in IM group, PT changes after vitamin K1 administration were 16.29 (SO 15.46) seconds in oral group and 11.58 (SO 10.62) seconds in IM group, it did not differ significantly (P=0.203).Conclusion Prothrombin time changes are not significantlydifferent between oral vitamin K1 and IM group.